2008
DOI: 10.1111/j.1365-2559.2008.03091.x
|View full text |Cite
|
Sign up to set email alerts
|

PAX‐5 is invariably expressed in B‐cell lymphomas without plasma cell differentiation

Abstract: PAX-5 is the most sensitive and reliable immunohistochemical marker for B-cell malignancies. Lack of PAX-5 expression correlates with the presence of marked plasma cell differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 48 publications
0
34
0
2
Order By: Relevance
“…Immunophenotypic expression patterns of DLBCL include positivity for various pan B-cell markers such as CD19, CD20, CD22, CD79a, PAX-5, and demonstration of immunoglobulin surface light chain restriction by flow cytometry in the majority of cases 63. The presence of positive PAX-5 immunostaining has been strongly associated with B-cell differentiation as PAX-5 is a B-cell restricted transcription factor 81,82. Staining for CD10, bcl-6, and MUM-1 are usually routinely performed in order to distinguish GCB from non-GCB DLBCL.…”
Section: Biomarkers Used In Hiv-nhl Diagnosis/prognosismentioning
confidence: 99%
“…Immunophenotypic expression patterns of DLBCL include positivity for various pan B-cell markers such as CD19, CD20, CD22, CD79a, PAX-5, and demonstration of immunoglobulin surface light chain restriction by flow cytometry in the majority of cases 63. The presence of positive PAX-5 immunostaining has been strongly associated with B-cell differentiation as PAX-5 is a B-cell restricted transcription factor 81,82. Staining for CD10, bcl-6, and MUM-1 are usually routinely performed in order to distinguish GCB from non-GCB DLBCL.…”
Section: Biomarkers Used In Hiv-nhl Diagnosis/prognosismentioning
confidence: 99%
“…It has been reported that PAX5 is expressed in most B-LPDs (Dong et al, 2008). Moreover, a large proportion of B-LPDs show a limited response to chemotherapy.…”
Section: Pax5-positive Cells Are More Resistant To Chemotherapy Drugsmentioning
confidence: 99%
“…Deregulation of PAX5 has been associated with various types of tumorigenesis (Cazzaniga et al, 2001;Kanteti et al, 2009;Kozmik et al, 1995;Kubetzko et al, 2004;Stuart et al, 1995), especially in B-cell malignancies, such as lymphoma and lymphocytic leukemia (Cobaleda et al, 2007;Krenacs et al, 1998). PAX5 expression is prevalent in B-LPDs, but not in plasma B-cell malignancies (Dong et al, 2008). In addition, about 30% of multiple myeloma cases have been found to be accompanied by PAX5 expression (Lin et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This marker is now routinely used in hematolymphoid cases and has been shown to be positive in cases of B-lymphoblastic leukemia, NHL of B-cell origin lacking plasmacytic differentiation, and cases of classical Hodgkin's lymphoma [11, 17, 18]. Importantly, this marker remains positive in cases of lymphoma in which patients have been treated with rituximab, a drug which targets the CD20 molecule.…”
Section: Discussionmentioning
confidence: 99%